Participation intention of activity-oriented program of local residents of rural and mountain villages: policy implication for the eco-mountain village project - Lee, Dukjae; Kim, Jong-Ho; Jeon, Jun-Heon (2008)
Factors for promoting the resident participation in mountain villages are suggested to introduce the activity-oriented program of green tourism using a multinomial logit model(MNLM). Direct surveying, using a structured questionnaire was performed on local residents in the different types of rural tourism villages such as mountain villages, agricultural themedvillages, and the mixed types of villages. The MNLM revealed that participation intention in the program was significantly higher for males, those with lower education, and residents in mountain villages. The participation intention of the program had a negative relationship with the increase of expected problems not from the program itself, but from the results of the program such as income distribution and nature destruction. Participation intention also increased with the indirect effects of an investment by the Village Development Project, such as local cooperativeness, public mind, etc. It was suggested that to introduce the activity-oriented program in mountain villages, negative effects from the results had to be minimized, and positive effects from the indirect changes between local residents had to be maximized through better communication and policy endeavors.